Nucleic acid therapeutics: Past, present, and future - Sajid Naeem; Ju Zhang; Yang Zhang; Yu Wang (Molecular Therapy: Nucleic Acids)
Nucleic acid therapeutics have become increasingly recognized in recent years for their capability to target both coding and non-coding sequences. Several types of nucleic acid modalities, including siRNA, mRNA, aptamer, along with antisense oligo, have been approved by regulatory bodies for therapeutic use. The field of nucleic acid therapeutics has been brought to the forefront by the rapid development of vaccines against COVID-19, followed by a number of approvals for clinical use including much anticipated CRISPR-Cas9. However, obstacles such as the difficulty of achieving efficient and targeted delivery to diseased sites remain. This review provides an overview of nucleic acid therapeutics and highlights substantial advancements, including critical engineering, conjugation, and delivery strategies, that are paving the way for their growing role in modern medicine.